2011
DOI: 10.1111/j.1365-2559.2011.03885.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent copy number gains of ACVR1 and corresponding transcript overexpression are associated with survival in head and neck squamous cell carcinomas

Abstract: These findings suggest that copy number alterations at 2q24 can be involved in ACVR1 overexpression, which is associated with longer overall survival in laryngeal carcinomas. To our knowledge, this is the first report indicating the relevance of ACVR1 expression in head and neck cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…In HNSCC diagnostics, no genomic test has been adopted widely, although HPV infection can be diagnosed using in situ hybridisation methods in addition to p16 staining . Further, copy number increases of ACVR1, EGFR, YWHAZ and GST‐pi have been reported to associate with survival, chemoresistance and malignancy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In HNSCC diagnostics, no genomic test has been adopted widely, although HPV infection can be diagnosed using in situ hybridisation methods in addition to p16 staining . Further, copy number increases of ACVR1, EGFR, YWHAZ and GST‐pi have been reported to associate with survival, chemoresistance and malignancy .…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence in situ hybridisation (FISH) technique is used routinely to identify the genomic events in the diagnostics of several cancers including chronic myeloid leukaemia, breast cancer and lung adenocarcinoma . In HNSCC diagnostics, however, no routine genomic test is currently in standard use, even though copy number increase of several genes has been reported to associate with survival, chemoresistance and malignancy .…”
Section: Introductionmentioning
confidence: 99%
“…Significant gains at 2q24 were detected in most cases at frequencies varying from 3 to 35% (Ambrosio et al, 2011).…”
Section: Cytogeneticsmentioning
confidence: 92%
“…Ambrosio et al (2011) reported that copy number alterations of 2q24.1 were associated with ACVR1 overexpression and with longer overall survival in laryngeal carcinomas. Prognosis In the study of Ambrosio et al (2011), it was described at first that oral cavity, laryngeal and pharyngeal carcinomas presented ACVR1 overexpression in agreement with 2q24 gains and amplifications detected by FISH analysis.…”
Section: Head and Neck Cancermentioning
confidence: 99%
See 1 more Smart Citation